New Copper Alloys Used to Make Products Intended for Contact with Drinking Water - Michał Chruściński (MDPI AG, 2021)
This article presents the results of tests conducted as part of a research project with the primary objective of developing new copper alloys with limited lead content. The new group of materials were created in a production plant. As part of tests, a group of 22 alloys were selected for testing in castability, structural characteristics and hardness. Based on the test results obtained, the group of alloys under study was narrowed down to nine. The mechanical properties of these alloys were determined in static tensile tests as well as in uniaxial upsetting tests at elevated temperature, on the basis of which the group of alloys under investigation was further narrowed to three. Further studies involved technological verification of the application of these alloys under industrial conditions. These alloys were subject to numerical forging analyses, along with forging tests, under semi-industrial conditions, where the degree of filling of a die impression at a specific temperature was measured using an optic scanner. The quality of production of the obtained forgings was evaluated macroscopically with simultaneous observations of the microstructure.